UJI TOKSISITAS FRAKSI n-HEKSAN DAUN BERUWAS LAUT (Scaevola taccada (Gaertn.) Roxb.) DENGAN METODE BRINE SHRIMP LETHALITY TEST - Rahmawati Rahmawati; Sitti Amirah; Andi Sulfika (Fakultas Farmasi UMI, 2012)
Research of effect toksisitas of n-heksan faction of the beruwas laut (Scaevola taccada (Gaertn.)Roxb.) leaf at prawn larva of Artemia salina Leach have been done as a mean to determine potency of toksisitas and value of LC50 beruwas laut (Scaevola taccada (Gaertn.)Roxb.) leaf. As control used n-heksan. Before treatment, prawn egg of Artemia salina Leach incubated at some stage and after 48 hours prawn larva of Artemia salina Leach are ready to given treatment. Hereinafter n-heksan faction of beruwas laut (Scaevola taccada (Gaertn.)Roxb.) leaf with concentration 0,1 ; 1 ; 10 ; 100 µg/ml in sea water enhanced 10 prawn larvas. For control, done same treatment. Perception done after 24 hours treatment by counting dead prawn larva. Result of perception indicate that value of LC50 n-heksan faction of beruwas laut (Scaevola taccada (Gaertn.)Roxb.) leaf 4,17 ± 2,59 µg/ml. So that can be expressed that n-heksan faction of beruwas laut (Scaevola taccada (Gaertn.)Roxb.) leaf have potency as anticancer, this matter is based by standard of Meyer (1982) expressing that a natural materials compound have potency of anticancer if value of LC50 <1000 µg/ml. Key word : Toksisitas Test, Scaevola taccada (Gaertn.)Roxb, Brine Shrimp Lethality Test